2020
DOI: 10.1038/s41380-020-0724-6
|View full text |Cite
|
Sign up to set email alerts
|

Potential depression and antidepressant-response biomarkers in human lymphoblast cell lines from treatment-responsive and treatment-resistant subjects: roles of SSRIs and omega-3 polyunsaturated fatty acids

Abstract: While several therapeutic strategies exist for depression, most antidepressant drugs require several weeks before reaching full biochemical efficacy and remission is not entirely achieved in many patients. Therefore, biomarkers for depression and drug-response would help tailor treatment strategies. This study made use of banked human lymphoblast cell lines (LCLs) from normal and depressed subjects; the latter divided into remitters and non-remitters. Due to the fact that previous studies have shown effects on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Therefore, cell models are often combined with studies on rodent models of depression to determine the cellspecific antidepressant mechanisms of drugs. 100,101…”
Section: Sh-sy5y Cellsmentioning
confidence: 99%
“…Therefore, cell models are often combined with studies on rodent models of depression to determine the cellspecific antidepressant mechanisms of drugs. 100,101…”
Section: Sh-sy5y Cellsmentioning
confidence: 99%
“…Earlier studies that employed more cumbersome cAMP assays suggested that attenuated PGE1 in platelets ( 32 ) and impaired β–adrenergic signaling in white blood cells ( 31 ) could be associated with both depression and clinical improvement. It is noteworthy, however, that, in lymphoblasts from depressed subjects we observed increased cAMP signaling which was reversed by antidepressant treatment ( 45 ). Unlike platelets, lymphocytes are negatively affected by cAMP, and attenuated cAMP is “favorable” for the lymphocyte.…”
Section: Discussionmentioning
confidence: 73%
“…208,209 These changes may partly account for the compounded antidepressant effects of n-3 PUFAs and selective serotonin reuptake inhibitors (SSRIs). 210 Contrastingly, treatment with the exogenous n-6 PUFA, arachidonic acid, showed no effect on the density of 5-HT 1A -R, its agonist affinity, the coupling efficiency between 5-HT 1A -R and G-proteins, or the activation ability of the 5-HT 1A -R to interact with G-proteins. 211 The most recent structure of porcine SERT, derived from native brain tissue, uncovered a lipid-like density that penetrates both TM10 and TM11 and the transporter itself.…”
Section: Acsmentioning
confidence: 96%
“…As a result, they influence the interaction, organization, fluidity, and clustering degree of lipid rafts. Supplementation with n-3 PUFAs can enhance hippocampal expression of 5-HT 1A -R and reverse depression-like behavior observed in postpartum depression models and during combined chronic mild stress and maternal separation. , These changes may partly account for the compounded antidepressant effects of n-3 PUFAs and selective serotonin reuptake inhibitors (SSRIs) . Contrastingly, treatment with the exogenous n-6 PUFA, arachidonic acid, showed no effect on the density of 5-HT 1A -R, its agonist affinity, the coupling efficiency between 5-HT 1A -R and G-proteins, or the activation ability of the 5-HT 1A -R to interact with G-proteins …”
Section: Lipid Regulation Of the 5-ht Synapsementioning
confidence: 99%